1982
DOI: 10.1139/v82-430
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active acyclonucleoside analogues. II. The synthesis of 9-[[2-hydroxy-1-(hydroxymethyl)ethoxy]methyl]guanine (BIOLF-62)

Abstract: Can. J . Chem. 60, 3005 (1982). The chemical synthesis of 9-[[2-hydroxy-l-(hydroxymethyl)ethoxy]methyl]guanine is described. This compound, known a s BIOLF-62, is active against herpesviruses. This compound is a member of a novel class of nucleoside analogues which lacka rigid carbohydrate ring, but which possess all of the functional groups of naturally occurring deoxynucleosides. I The search for biologically active molecules has ' focused a great deal of attention on modified nucleosides (1-3). For several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…In the 1 H NMR spectra of each 7 and 8 appeared a signal of acetyl groups and disappeared that of tosyl groups. Acylation of 7 at room temperature with acetyl bromide leads to the mixture of 9 and 10 in ratio 1/3 as shown by 1 H NMR. And the minor synthon 9 was equally obtained by acylation of 8 in 97% yield.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the 1 H NMR spectra of each 7 and 8 appeared a signal of acetyl groups and disappeared that of tosyl groups. Acylation of 7 at room temperature with acetyl bromide leads to the mixture of 9 and 10 in ratio 1/3 as shown by 1 H NMR. And the minor synthon 9 was equally obtained by acylation of 8 in 97% yield.…”
Section: Resultsmentioning
confidence: 94%
“…The discovery of the two structural isomers acycloguanosines [1][2][3][4][5][6] : 9-(1,3-dihydroxy-2-propoxymethyl) guanine (DHPG, 1) and 9-(2,3-dihydroxy-1-propoxymethyl) guanine (iso-NDG, 2) ( Figure 1) as the effective and highly selective antiviral drugs for the treatment of herpes simplex virus (HSV) infections has stimulated an extensive search for acyclic nucleosides that are more potent antiviral agents. So far, the structure-activity studies have shown that the side chain of acyclic nucleosides plays a main role in the antiviral activity (phosphorylation).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In view of its substantial commercial importance, several synthetic routes were developed for ganciclovir using guanine, 3,4 acetylguanine, 3 2-amino-6-chloropurine, 3,5 tetraacetylguanosine, 6,7 and diacetylguanine 2 (Figure 1), [8][9][10][11] as the source of guanine moiety. Coupling of one of such guanine derivatives with an appropriately protected, activated glycerol derivative such as 1,3-diacetoxy-2-acetoxymethoxy propane or 1,3-dibenzyloxy-2-acetoxymethoxy propane is the commonly employed strategy to access ganciclovir.…”
Section: Introductionmentioning
confidence: 99%
“…The successful development of acyclovir I (ACV) [1,2], 9-[(2-hydroxyethoxy)-methyl]guanine, and ganciclovir II (DHPG) [3,4] as excellent antiviral agents have stimulated the synthesis and biological evaluation of a wide variety of acyclic nucleosides modified either in the base moiety or the acyclic part.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional and common synthetic methods for the preparation of acyclic nucleosides and nucleotides involve the coupling reaction of heterocyclic bases with ␣-halo [5][6][7] or acetoxymethyl ethers catalyzed by various Lewis acids or bases [7,8], e.g., HMDS [5,6], SnCl 4 , Hg(CN) 2 , (CH 3 ) 3 SiClO 4 , (CH 3 ) 3 SiSO 3 C 4 F 9 [9,10], and natural phosphates (NP) [6] to afford the regioselective N-alkylation of the nucleobases, i.e., acyclonucleoside.…”
Section: Introductionmentioning
confidence: 99%